Excellent patient-reported long-term quality of life after an Ivor Lewis esophagectomy for cancer - Blumenthaler, Alisa N.; Feizpour, Cyrus A.; Jalal, Shadia I.; Lopez, Kevin J.; Ramchandani, Neal K.; McAlister, Joshua; Perkins, Susan M.; Han, Yan; Rieger, Karen M.; Brooks, JoAnn; Kesler, Kenneth A. (Frontiers in Surgery, 2025)
BackgroundLong-term health-related quality of life (HRQOL) may be impacted by upper gastrointestinal tract dysfunction following esophagectomy in up to two-thirds of patients. After esophagectomy, the stomach conduit is passively relying on gravity for drainage. Any resistance to flow through the stomach conduit, therefore, has the potential to significantly impact long-term HRQOL. We have previously reported a side-to-side esophagogastric anastomotic technique, which optimizes anastomotic diameter and vascularity, resulting in a low incidence of leaks and strictures. A wide pyloroplasty is another component of this technique that minimizes resistance to flow. In this study, we aimed to evaluate the long-term HRQOL and esophageal-specific QOL in cancer patients who underwent this surgical approach.MethodsFrom 2009–2015, 245 consecutive patients underwent Ivor Lewis esophagectomy for cancer utilizing a consistently performed technique including esophagogastric anastomosis, conduit construction, and surgical pyloric drainage. Functional Assessment of Cancer Therapy-Esophageal (FACT-E) questionnaires were distributed to surviving patients. Routine postoperative fluoroscopic contrast studies were used to characterize conduit function as normal or delayed emptying. Summary statistics for FACT-E and subscales were analyzed.ResultsEighty-five (34.7%) patients were alive at a median of 58 months and 66 (77.6%) of these patients participated in the study. Survey participants had higher Charlson-Comorbidity Indices (p = 0.01) and pathologic tumor stages (p = 0.04) compared to non-participants. Participants reported overall very favorable symptom profiles on the Esophageal Cancer Subscale (median, IQR: 55, 48.9–62.0; total possible: 68.0). Early satiety was the only item with >33% negative responses (n = 30, 45%). FACT-E total scores were also favorable (median, IQR: 146.0, 126.0–161.0; total possible: 176.0). Delayed emptying, identified in 17 (27.4%) participants, was not associated with HRQOL scores.ConclusionPatient-reported long-term HRQOL following a consistently performed esophagectomy technique was very favorable in all subscales, but symptoms of early satiety persisted. Delayed postoperative conduit emptying did not impact HRQOL. These results should be compared to other consistently performed esophagectomy techniques.